Proses, Analisis Dan Strategi Investasi Di Pasar Modal - Indahwati Indahwati; Ni ketut Yulia Agustini (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The capital market carries out transactions online, which provides opportunities for people to invest. It is very impressive that it seems as if the capital market is not affordable for the public and the ease of access to the capital market as an investment opportunity is less likely to be captured by the majority of the public due to a lack of understanding about investing in the capital market. This study aims to provide understanding and education regarding processes and strategies in the capital market, so that the public can actively participate in investment activities in the capital market. This study is a qualitative descriptive study by developing an investment scheme and strategy that provides illustrations to facilitate understanding of investors in the capital market. The results of this research are a comprehensive picture of investing starting with the investment process, stock trading mechanisms, various aspects of analysis and investment strategies, so that investors can make investment decisions. The implication of this study is that investors need to determine their investment objectives and have an understanding of investing in the capital market before making investment decisions.